Doing Unto Others: Applied Anthropology, Collaborative Research and Native Self-determination - Warry, Wayne (Culture, 1990)
This paper examines applied anthropology in relation to Native self-determination. Adherence to the principle of self-determination in research produces a fundamental shift from independent to collaborative research. The paper discusses Native people’s involvement in research design and the role of aboriginally defined policy in shaping the parameters of applied research. The research-policy nexus remains dominated by non-Native practitioners and bureaucrats employing inappropriate methodologies. Anthropologists can strengthen interdisciplinary research by advocating the use of participatory and other qualitative research techniques which Native people view as ‘culturally appropriate’.